2008
DOI: 10.1021/ac701887p
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pousão Pigments and Extenders by Micro-X-ray Diffractometry and Infrared and Raman Microspectroscopy

Abstract: Seventeen samples from paintings by the distinguished 19th century Portuguese painter, Henrique Pousão, were characterized by micro-X-ray diffractometry and infrared and Raman microspectroscopy. The main advantages and limitations of each technique for pigment identification are outlined, revealing the need for the use of complementary techniques. Pousão's palette is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…However, the intentional presence of lead sulfate cannot be fully disregarded. This compound has been rarely used as a white pigment, although its use has been reported at the end of the 19th century, and it has been found in some paintings of the same period as reported by Correia et al Lead sulfate is furthermore the responsible for the band at 979 cm −1 observed in the Raman spectra of black and brown motifs described above.…”
Section: Resultsmentioning
confidence: 66%
“…However, the intentional presence of lead sulfate cannot be fully disregarded. This compound has been rarely used as a white pigment, although its use has been reported at the end of the 19th century, and it has been found in some paintings of the same period as reported by Correia et al Lead sulfate is furthermore the responsible for the band at 979 cm −1 observed in the Raman spectra of black and brown motifs described above.…”
Section: Resultsmentioning
confidence: 66%
“…In detail, the pinkish color was measured on the skin of both women (points 12.A and 13.A) and angel (point 8.A). The obtained results suggest the use of a mixture of hematite (Fe 2 O 3 ; Raman bands at 620 and 412 cm -1 [7]) and lead white (2PbCO 3 ÁPb(OH) 2 ; Raman band at 1052 cm -1 [8]). Additionally, the 785-nm laser detected the presence of red lead (Pb 3 O 4 ) (peak at 548 cm -1 ).…”
Section: Reddish Huesmentioning
confidence: 80%
“…However, the elements detected may also occur from extenders added to a synthetic variety. Clay minerals were not detected by Raman spectroscopy, which may relate to the fact that they are weak Raman scatters, and thus difficult to identify by this technique, particularly when present with other compounds [16,17].…”
Section: Brown Central Areamentioning
confidence: 95%
“…This was likely due to the pigment's weak Raman signal, which is easily masked in the presence of other compounds [3,16]. Zinc white was detected by SEM-EDX and moreover Zn was detected in combination with chrome green, ultramarine, cadmium red and dinitraniline orange PO5 in KSa/1948, KSb/1955, KSd/1964and KSf/1990 respectively, indicating the possible presence of zinc white in these layers too.…”
Section: àmentioning
confidence: 99%